2020
DOI: 10.1002/marc.202000141
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Methacrylate Polymer/Reduced Graphene Oxide Nanocomposite Particles Stabilized by Poly(ionic liquid) Block Copolymer via Miniemulsion Polymerization

Abstract: Poly(n‐butyl methacrylate) (PnBMA)/reduced graphene oxide (rGO) nanocomposite films are prepared using two different routes. The first route involves preparation of PnBMA nanoparticles containing homogeneously dispersed rGO nanosheets by miniemulsion polymerization using a block copolymer of ionic liquid (IL) monomer and nBMA. The IL units act as adsorption sites for rGO whereas BMA units provide solubility in the BMA monomer droplets. Nanocomposite films obtained from miniemulsion polymerization exhibit highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…[4][5][6] Many research groups, including our own, have used graphene oxide (GO) nanosheets to stabilize oil-in-water emulsions, with more recent efforts towards modifying the surface of the nanosheets to enable them to stabilize other fluid-fluid combinations (e.g., ionic liquid-water, ionic liquid-oil, oil-oil, etc.). [7][8][9][10][11][12][13][14][15][16][17] We have also recently demonstrated that transition metal carbide (MXene) and transition metal oxide (cobalt oxide) nanosheets can stabilize oil-in-water emulsions, if first flocculated by simple inorganic salt such as NaCl. 18,19 Compared to GO, these inorganic 2D surfactants are expected to not only provide kinetic stability to the emulsion, but to also impart favorable performance properties to any composite structures formed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Many research groups, including our own, have used graphene oxide (GO) nanosheets to stabilize oil-in-water emulsions, with more recent efforts towards modifying the surface of the nanosheets to enable them to stabilize other fluid-fluid combinations (e.g., ionic liquid-water, ionic liquid-oil, oil-oil, etc.). [7][8][9][10][11][12][13][14][15][16][17] We have also recently demonstrated that transition metal carbide (MXene) and transition metal oxide (cobalt oxide) nanosheets can stabilize oil-in-water emulsions, if first flocculated by simple inorganic salt such as NaCl. 18,19 Compared to GO, these inorganic 2D surfactants are expected to not only provide kinetic stability to the emulsion, but to also impart favorable performance properties to any composite structures formed.…”
Section: Introductionmentioning
confidence: 99%
“…). 7–17 We have also recently demonstrated that transition metal carbide (MXene) and transition metal oxide (cobalt oxide) nanosheets can stabilize oil-in-water emulsions, if first flocculated by simple inorganic salt such as NaCl. 18,19 Compared to GO, these inorganic 2D surfactants are expected to not only provide kinetic stability to the emulsion, but to also impart favorable performance properties to any composite structures formed.…”
Section: Introductionmentioning
confidence: 99%
“…1 Combining the features of polymers and ions, these ionized polymers (IPs) have received tremendous attention owing to the amazing advantages, such as excellent ionic conductivity, 2,3 chemical compatibility, 4,5 non-flammability 6,7 and electrochemical stability, 8,9 and so forth. By introducing different cationic and anionic ions onto polymeric backbone, the IPs based materials with defined structures and functions have been successfully exploited, and widely used in polymer chemistry, electrochemistry, material science and energy science field, [10][11][12][13][14] and so forth. Typically, the IPs are dominantly prepared via two approaches, polymerization of ionic liquid monomers (ILMs) and post-modification of certain polymeric precursors.…”
Section: Introductionmentioning
confidence: 99%